O TRATAMENTO RESTAURADOR ATRAUMÁTICO NOS CURSOS DE ODONTOLOGIA DO ESTADO DO PARANÁ NA PERCEPÇÃO DE ACADÊMICOS E PROFISSIONAIS: ESTUDO DE SEGUIMENTO DE SEIS MESES APÓS A FORMATURA - Martins, Alessandra de Souza (2016)
This study investigated the attitudes of dentists on ART since the last month of graduation until six months after graduation, in order of the interest of using the strategy in the public and private service. This is a follow-up study with a sample in the first stage of the research consisted of 400 graduating students of dentistry courses 10 colleges of the Paraná state and the second time, these 400 students, 112 answered the questionnaire, now as professionals six months graduated. The investigated variables involved: general characteristics of participants, subjects in which ART was approached and practiced during graduation; knowledge built on the strategy; instructions for use; self-perception as security for the implementation of technical and credibility attributed to ART; employment intention of the strategy; workplace; participation in professional courses geared to ART; Use of the ART after graduation; results and barriers that involve the application of this strategy. Associations between variables were assessed using the chi-square test and exact Fisher. All participating colleges address the ART and this approach occurs mainly in the disciplines of Pediatric Dentistry and Public Health. Most individuals in the two stages of the study, believes that the ART strategy interrupts the carious process and prevents tooth loss, but the intention of use, among academics, and use, for professionals, is more directed to the public service than to private practice. Also in the two moments of the research atraumatic restorations were more suitable for primary teeth and considered provisional interventions. The use of claims in private practice was significantly associated to academic who used ART during graduation (p = 0.006); have the intention not to use the strategy in the private service was significantly higher among those who do not indicate ART for permanent teeth of adults and adolescents (p <0.001). The public school students have more contact with the ART strategy in other disciplines, as well as Public Health and Pediatric Dentistry, and students of private colleges were the most indicated ART for permanent teeth. The inapplicability of ART, after graduation, was significantly associated with the professionals who work exclusively in the private service (p = 0.012) and the study subjects began to indicate more ART for permanent teeth of pregnant women (p = 0.005), elderly (p = 0.002), adults (p <0.001) and females (p <0.001), and considers it as definitive procedure more (p = 0.008). This study identified that the ART is not considered a definitive therapy, and less suitable for the permanent dentition and for private practice. In addition, continuing education experienced by professionals seems to interfere in their attitudes towards ART strategy.